ANALISIS PELATIHAN PENGEMUDI BUS RAPID TRANSIT (BRT) TRANS SEMARANG - Kesani, Fairuz Ardiaz; Hanani, Retna; Rahman, Amni Zarkasyi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Driver training is a program aimed at enhancing the skills, knowledge, and safety awareness of Bus Rapid Transit (BRT) Trans Semarang. Training for drivers are necessary to improve the safety and service quality of BRT Trans Semarang in accordance with the Minimal Service Standards. However, in reality, there are still many complaints from the community regarding Trans Semarang BRT drivers. The purpose of this research is to understand the training of Trans Semarang BRT drivers and the influencing factors. This research uses a descriptive qualitative method with data collection techniques in the form of interviews and literature studies. The results of the study show that the training of Trans Semarang BRT drivers have been quite good, but there are still some dimensions that need improvement. Supporting factors influencing the training of Trans Semarang BRT drivers include top management support, the commitment of specialists and generalists, technological advancements, and learning styles. Meanwhile, inhibiting factors include organizational complexity.